Study of lipid profile in polycystic ovarian syndrome: a case control study in tertiary care hospital - Marbaniang, Racheal Sweet; Yanglem , Ajitkumar Singh; Kshetrimayum, Victoria; Naorem, Sangeeeta; Laithangbam, Rosyka; Ashem, Florida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common causes of endocrine dysfunction in women of reproductive age. Dyslipidaemia plays an important role in the development of PCOS. Lipid abnormalities which include elevated low-density lipoprotein and triglyceride levels and reduced high-density lipoprotein levels are often found in women with PCOS and thus they are associated with long-term risk of coronary heart disease. The study aims to estimate lipid profile levels in patients with polycystic ovarian syndrome (PCOS) taken as cases and normal healthy subjects taken as controls. Methods: This is a case control study conducted in the Department of Biochemistry in collaboration with Department of Obstetrics and Gynaecology, RIMS, Imphal. Fasting blood samples were collected from cases and controls and lipid parameters were estimated. Forty-five cases of PCOS patients in the age group of 18-44 years diagnosed according to Rotterdam criteria and forty-five age-matched healthy women with regular menstrual cycle taken as controls were recruited. Results: The mean±SD of age in cases was 26.38±4.85 years and control was 28.23±3.99 years. However, the difference was found to be statistically insignificant. The majority of cases were from urban areas which comprised of 62% and only 55.6% were from rural areas. The mean±SD for cholesterol, TG, LDL were 203.40±54.20 mg/dl, 163.26±69.49 mg/dl, 132.82±50.39 mg/dl respectively and was higher in cases compared to controls and the difference was statistically significant. However, the mean±SD of HDL in cases 24.81±2.31mg/dl was lower as compared to controls and the difference was statistically significant with p<0.05. Conclusions: PCOS is found to be associated with atherogenic lipid profile. Thus, it may be suggested that dietary control and improvement of living style to control dyslipidaemia should be taken up early in PCOS to prevent development of cardiovascular disease.